Don't behave like you live in a cave - Verdick, Elizabeth; Mark, Steve (Minneapolis, MN : Free Spirit Pub., 2010)
Explains how children can make smarter, more positive choices about how they behave at home and at school and, as a result, stay out of trouble, feel good about themselves, and get along better with family, friends, and teachers.
Includes index.
Keywords: Child psychology -- Juvenile literature; Children -- Conduct of life -- Juvenile literature; Etiquette for children and teenagers -- Juvenile literature